PENINGKATAN HASIL DAN EFISIENSI USAHATANI BUDIDAYA PADI SAWAH DENGAN SISTEM TANAM BENIH LANGSUNG (TABELA) - Hartono, Rudi; Gunawan, Gunawan (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2004)
Paddy still has the strategic role as staple food, so that effort to increase of its productivity become the attention various related parties. Continuously productivity pushed the researcher to study that has high product system efficiency in order to increase earnings of farmer and continuing farming system. Farming system that depressed the production cost through use fertilize according to land fertility per plant of tabela system disease operation pest by PHT and exploiting of farm resource. Study of tabela system paddy rice field was executed in Countryside Rimbo Recap, Sub district Curup, Regency Rejang Lebong broadly carpet 50 ha entangling 45 cooperator farmer. Location selected by purposive with the consideration that area represent central paddy in regency of Rejang L(jbong. Varieties used are IR 64. Direct seed plantsystem show a prospect by economizing labor used from 28 to 20 HOC, Increasing production of O.5 - 1.15 tontha either due manifestly can economize the labor from 28 becoming 10 HOC, increase product 0, 5 - 1,5 ton / ha dry shell of rice harvest. dry shell of rice eliminating negative impact of seedbed and quality of shell rice and also short crop age 11 - 17 day which is enlarge the opportunity of increase per plant intensity. This existence of great productivity and farmer earnings whiCh is to 15 - 20 % can be obtained by through product increase wide association and cost-saving production like labor fee, expense fertilize and also opportunity of exploiting farm resource